Philippines, Smallholder Livestock Production Dataset, 2000-2001 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The study draws on household survey data collected in 2000-2001. The survey was conducted in three hog producing cities in the provinces of Batangas and Laguna in Southern Luzon, Philippines. To understand why some smallholders participate in hog production and others do not, a total of 291 households were randomly identified from a stratified sample frame, of which 150 households were hog producers (including 50 small-scale contract farms) and 141 households were non-livestock raisers. The sampled smallholders are household-based backyard growers (who use their own capital and family labor) and/or semi-commercial growers (who employ hired labor and use external financing for livestock production) holding an inventory ranging up to 300 head of hogs at any given period. Some of the variables collected are: farm-specific output and inputs prices, quantity of output in kilograms liveweight, different types of activity, family and hired labor, value of breeding stock; value of buildings and equipment, different market outlets, household characteristics, access to information, credit, and veterinary services.